Proteomic evidence of methanotrophy in methane‐enriched hypolimnetic lake water. (1st July 2016) - Ullrich, Nina; Casper, Peter; Otto, Andreas; Gessner, Mark O.
Abstract: Freshwaters have recently been recognized as important sources of methane emitted to the atmosphere, and microbial methane oxidation at the oxic/anoxic interface is a key process controlling these emissions. We applied proteomics to determine enzyme expression patterns of methanotrophs in response to methane enrichment of lake water. In a small‐scale incubation experiment with natural bacterial communities we compared enzymes involved in methane metabolism between control and methane‐enriched hypolimnetic water simulating high (∼1 mM) and low (∼0.001 mM) methane concentrations at oxyclines in lakes. Methane was effectively consumed when the supply was high, reducing oxygen levels from 0.40 mM (12.9 mg L −1 ) to 0.09 mM (3.0 mg L −1 ), well below those in the controls. The dominant key enzyme of microbial methane oxidation, particulate methane monooxygenase, was identified in both enriched and control flasks, whereas enzymes potentially involved in methane metabolism via the RuMP pathway and serine cycle were essentially restricted to the enriched flasks. All enzymes had best sequence matches with type I methanotrophs, whereas no indication of type II or type X methanotrophs was found, even though four enzymes of the serine cycle were identified. Overall, our proteomic analysis provides convincing evidence that a suite of genes required for methanotrophy are quickly expressed when the presence of both methane and oxygen creates conditions characteristic of oxyclines in lakes.